2022
DOI: 10.1093/jxb/erac233
|View full text |Cite
|
Sign up to set email alerts
|

Functions and prospects of melatonin in plant growth, yield, and quality

Abstract: Melatonin (N-acetyl-5-methoxytryptamine) is an indole molecule widely found in animals and plants. Melatonin is well-known to improve plant resistance to various biotic and abiotic stresses due to its potent free radical scavenging ability while being able to modulate plant signaling and response pathways through mostly unknown mechanisms. In recent years, more and more studies have shown that melatonin plays a crucial role in improving crop quality and yield by participating in the regulation of various aspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 181 publications
0
35
0
Order By: Relevance
“…Since its discovery in plants, MT has attracted more and more attention from plant scientists due to its involvement in plant growth, development, photosynthesis, rooting, seed germination, biotic, and abiotic stress responses ( Arnao and Hernández-Ruiz, 2014 ; Reiter et al., 2015 ; Debnath et al., 2019 ; Khan et al., 2020 ; Sun et al., 2020 ; Li et al., 2021 ; Wang et al., 2022 ). The efficacy of MT in reactive oxygen species (ROS) scavenging and antioxidant defense responses are the two major mechanisms to cope with major abiotic stresses ( Sun et al., 2020 ; Tiwari et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery in plants, MT has attracted more and more attention from plant scientists due to its involvement in plant growth, development, photosynthesis, rooting, seed germination, biotic, and abiotic stress responses ( Arnao and Hernández-Ruiz, 2014 ; Reiter et al., 2015 ; Debnath et al., 2019 ; Khan et al., 2020 ; Sun et al., 2020 ; Li et al., 2021 ; Wang et al., 2022 ). The efficacy of MT in reactive oxygen species (ROS) scavenging and antioxidant defense responses are the two major mechanisms to cope with major abiotic stresses ( Sun et al., 2020 ; Tiwari et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in sweet cherry, the phytomelatonin content reaches a maximum at early stages of fruit set and development, and then decreases at the start of ripening ( Tijero et al , 2019 ). External application of melatonin retards senescence and extends the postharvest life of fruits during storage via regulation of ROS, reactive nitrogen species (RNS), and ethylene ( Arnao and Hernández-Ruiz, 2020a , 2021 ; Aghdam et al , 2022 ; Corpas et al , 2022 ; K. Wang et al , 2022 ).…”
Section: Phytomelatonin Signaling In Plant Growth and Developmentmentioning
confidence: 99%
“…Seed formation, growth, maturation, and germination are crucial developmental stages in the life cycle of seed plants. Several studies have found that melatonin can promote seed germination under stress conditions, especially in old or damaged seeds, improving germination rate probably through fit hormonal balance ( K. Wang et al , 2022 ). In contrast, Lv et al (2021) and Yin et al (2022) have shown that high concentrations of melatonin inhibit Arabidopsis seed germination and seedling growth, possibly due to disorder in ABA, GA, and auxin balance.…”
Section: Phytomelatonin Signaling In Plant Growth and Developmentmentioning
confidence: 99%
“…Melatonin can be considered a biostimulant molecule; the use of melatonin in agriculture could be an alternative and sustainable method to the use of agrochemicals [ 3 , 4 ]; melatonin also has a positive potential in phytostimulatory activities [ 5 ] and genetic breeding [ 6 ]. A large number of studies have shown that melatonin has a powerful free radical scavenging ability to enhance plant resistance to various biotic and abiotic stresses and its regulative role in regulating plant signaling and response pathways [ 7 ]. For example, relatively low melatonin concentrations enhanced plant stress resistance, such as drought [ 8 ], salt [ 9 ], low temperature [ 10 , 11 ], high temperature [ 12 ], and heavy metal stress [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%